Hollow NiCoP Nanoprisms Derived from Prussian Blue Analogues as Bifunctional Electrocatalysts for Urea‐Assisted Hydrogen Production in Alkaline Media. Issue 51 (3rd November 2022) - Ding, Xueda; Pei, Lishun; Huang, Yuxin; Chen, Dongyang; Xie, Zailai
Abstract: Integrating the hydrogen evolution reaction (HER) and urea oxidation reaction (UOR) is an energy‐saving approach for electrolytic H2 production. Here, hollow NiCoP nanoprisms are derived from Prussian blue analogues by a combined self‐template coordination reaction and gas‐phase phosphorization strategy. Benefiting from the strong electron interaction, unique hollow nanostructure, and enhanced mass/charge transfer, NiCoP nanoprisms display outstanding alkaline HER and UOR performance. Specifically, low potentials of −0.052, −0.115, and −0.159 V for HER and ultralow potentials of 1.30, 1.36, and 1.42 V for UOR at current densities of 10, 50, and 100 mA cm −2 are obtained. Moreover, in a urea‐assisted water electrolysis system, NiCoP nanoprisms only require cell voltages of 1.36, 1.49, and 1.57 V to offer current densities of 10, 50, and 100 mA cm −2, about 170, 180, and 200 mV less than the traditional water electrolysis. Theoretical calculations indicate the Co substitution in Ni2 P promotes the adsorption and dissociation of water molecules, optimizes the desorption energy of active hydrogen atoms, and enhances the adsorption of urea molecules, thus accelerating the kinetics of HER and UOR. This work facilitates the application of hollow bimetallic phosphides in electrochemical preparation of clean energy and provides a successful paradigm for urea‐rich wastewater electrolysis. Abstract : Hollow NiCoP nanoprisms are fabricated by a combined self‐template coordination reaction and gas‐phase phosphorization strategy. Due to the unique hollow nanostructure, strong electron interaction, and enhanced mass/charge transfer, the well‐designed NiCoP nanoprisms exhibit excellent electrochemical performance for the hydrogen evolution reaction, urea oxidation reaction, and urea‐assisted overall water splitting in alkaline media.